Cost of an unforced error in tennis: a statistical approach - Attray, H.; Attray , S. (Coaching and Sport Science Review, 2021)
The objective of this paper is to (1) introduce a scientific way of measuring the cost of an unforced error in tennis during various match situations and (2) to provide a basis for players and coaches to choose the right strategy among extremely cautious and adventurous playing styles based on a statistical approach. To do this, we analyzed a total of 2,490 different match situations. The results of this study show that the cost of an unforced error varies greatly depending on the match situation. Players are better served by playing a high percentage, low-risk game in situations when the cost of an unforced error is higher than the median cost and adapt a high-risk approach when it is lower than the median cost.